2018
DOI: 10.18553/jmcp.2018.24.5.469
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Adherence to Chronic Disease Medications in Patients with Long-term Initial Medication Fills Using Indicators of Clinical Events and Health Behaviors

Abstract: This work was supported by an unrestricted grant from CVS Health to Brigham and Women's Hospital. Shrank and Matlin were employees and shareholders at CVS Health at the time of this study; they report no financial interests in products or services that are related to this subject. Spettell is an employee of, and shareholder in, Aetna. This research was previously presented at the 2016 Annual Conference of the International Society for Pharmacoepidemiology; August 25-28, 2016; Dublin, Ireland.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 29 publications
1
30
0
Order By: Relevance
“…As noted in a recent review, many of the factors identified as having an association with medication adherence are inconsistent across studies and are not modifiable . More recent studies have started to examine the relative contribution of different risk factors for non‐adherence across a range of treatments for long‐term conditions: prior non‐adherence and trajectories of use of treatment appear to be consistent and clinically relevant factors …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As noted in a recent review, many of the factors identified as having an association with medication adherence are inconsistent across studies and are not modifiable . More recent studies have started to examine the relative contribution of different risk factors for non‐adherence across a range of treatments for long‐term conditions: prior non‐adherence and trajectories of use of treatment appear to be consistent and clinically relevant factors …”
Section: Discussionmentioning
confidence: 99%
“…A wide range of factors have been shown to be associated with poor adherence to diabetes medications including clinical features (female sex, younger age, non‐white ethnicity), other comorbidities such as depression, the class of medication and other prescriptions (medications after first‐line metformin, total daily pill burden), healthcare system (insurance, medication costs) and psychosocial factors (medication beliefs, physician trust) . In addition, adherence to previous medications has been shown to help improve predictive ability for determining adherence to statins and, more recently, in patients with cardiometabolic disorders . Adherence differs by medication class, with adherence being poorer with first‐line metformin therapy .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifth, our definition of medication adherence assumes observed medication supply and/or prescription fills equate with actual medication‐taking behavior. While this definition may not be entirely accurate, use of PDC and administrative claims are well‐documented in the scientific literature . Lastly, our analytic models did not account for the effect of the coverage gap on predicting adherence.…”
Section: Discussionmentioning
confidence: 99%
“…Second, predicting issues of nonadherence, especially those related to access and convenience, could help determine which patients are eligible for long‐term medication use. Increasing medication supply per prescription (eg, 90‐day supply) has become a common method used by payers to reduce refill requests and address adherence problems . Third, predicting adherence problems also has potential reimbursement implications.…”
Section: Discussionmentioning
confidence: 99%